MOF@PEDOT Composite Films for Impedimetric Pesticide Sensors (Global Challenges 2/2020). Issue 2 (3rd February 2020) - Sappia, Luciano D.; Tuninetti, Jimena S.; Ceolín, Marcelo; Knoll, Wolfgang; Rafti, Matías; Azzaroni, Omar
Abstract : Research efforts are increasingly focused on the development of portable devices for the on‐site evaluation of pesticide residues in food. In article 1900076, Jimena S. Tuninetti and co‐workers develop a chemi‐impedimetric sensor of imazalil using metal–organic frameworks (MOFs) incorporated into a conductive PEDOT composite film. The high affinity of the pesticide for the MOF crystallites allows for outstanding sensitivity to imazalil in the range of 15 ppb to 1 ppm.